Exploring the Role of Ginkgo biloba in Investigating 7L1X in Triple-Negative Breast Cancer Through Integrative Bioinformatics - Vignesh Gopinath (International Journal of Bioinformatics and Computational Biology, 2024)
Objectives: Triple-negative breast cancer is a very dangerous form of cancer that affects mostly Hispanic and African American women above the age of 40. It represents approximately 15–20% of the global cancer incidence. This experiment aims to investigate the use of Gingko biloba in the treatment of the disease triple-negative breast cancer. Methods: We use a variety of online tools, and websites, including the Indian Medicinal Plants, Phytochemistry, and Therapeutics database, to extract the phytochemical compounds, the PubChem website to obtain the canonical SMILES, and the 2-D format is used to download the SDF files, the protein database website to download the protein files in protein database format, the Ramachandran’s Plot. This way, we can visualize that in Discovery Studio BIOVIA app. Then, the Swiss ADME website is used to find which compounds satisfy Lipinski’s rule, and the other conditions. Result: The results showed that the compounds Afzelin, D-Glucuronic acid, Gingketin, Acacetin, Quercetin, Isoginkgetin, and Genkwanin satisfy all the criteria, and could be further used in the treatment of TNBC. Conclusion: The observations suggest that the below-mentioned phytochemical compounds: Afzelin, D-Glucuronic acid, Gingketin, Acacetin, Quercetin, Isoginkgetin, and Genkwanin seem to satisfy all the conditions for it to be used in the ADME testing and analysis and can be used in the treatment of TNBC.
Keywords: CK2 alpha kinase; Ginkgo biloba; Ramachandran’s Plot; Triple-negative breast cancer (TNBC); breast cancer gene-1 (BRCA)